Pengaruh Sistem Hidroponik dan Media Tanam Terhadap Pertumbuhan dan Produksi Tanaman Sawi (Brassica rapa L) - Nur Hafijah; Tutik Nugrahini; Zainudin Zainudin (Universitas Widya Gama Mahakam, 2019)
Effect of hydroponic systems and planting media on growth and production of mustard plants (Brassica rapa L) The purpose of this study was to determine the effect of systems and different hiodroponic growing media on the growth and production of mustard plants. This research was conducted for 3 months, starting from June to September 2017. The research location was located in Embalut village, Tenggarong Sub-District, across the Kutai Kartanegara Regency, East Kalimantan Province. The research design used was Completely Randomized Design (CRD) consisting of 2 factors with 5 replications, the first factor was the hydroponic system consisting of 3 (three) levels, namely: system wick (s?), system NFT (s?), system DFT (s?) . The second factor is m? = husk charcoal, m? = Cocopeat, m? = Rockwool. The results of this study indicate that the treatment system has a very significant effect on the average number of leaves, leaf width, plant height, leaf width of mustard plants aged 4, 5 and 6 mst, did not significantly affect the fresh weight of mustard plants. The media treatment did not affect the average number of leaves, plant height, leaf width of plants at 4, 5, 6 and fresh weight of plants did not have significant effect. The effect of the best system treatment on the growth of mustard plants produced by the NFT system (s?), the best media treatment for the growth of mustard plants was produced by the Cocopeat treatment (m?). The highest interaction with the fresh weight of mustard plants was produced by a combination of treatment s?xm?.;